Outcomes of antifungal prophylaxis in high-risk liver transplant recipients - Hadley, S.; Huckabee, C.; Pappas, P.G.; Daly, J.; Rabkin, J.; Kauffman, C.A.; Merion, R.M.; Karchmer, A.W. (Transplant infectious disease, 2009)
: Antifungal prophylaxis for liver transplant recipients (LTRs) is common among patients considered at high risk of infection, but optimal prophylaxis duration and drug has not been defined. This study aimed to assess the effects of 14 days of antifungal therapy prophylaxis in reducing proven invasive fungal infections (IFI) in high‐risk subjects. Eligible subjects who met 2 or more risk criteria were randomized 1:1 to the treatment arms (liposomal amphotericin B or fluconazole) and were followed for 100 days post transplantation for evidence of IFI. The study was designed to enroll 300 subjects, but was closed early for insufficient enrollment. A total of 71 subjects were enrolled and randomized. Two‐thirds of subjects completed 14 days of study therapy. Ten subjects developed proven or probable IFI with Candida species (9 subjects) and Cryptococcus neoformans (1 subject); rates were similar in the 2 treatment arms. Eleven subjects died, but no death was attributed to study drug or IFI. In summary, high‐risk LTRs tolerated antifungal prophylaxis well, and rates of IFI were lower than previously reported in untreated high‐risk LTRs.